Eros and Creativity in Russian Religious Renewal: The Philosophers and the Freudians - Crone, Anna Lisa (Russian History and Culture Ser., 2010)
Eros and Creativity in Russian Religious Renewal explores a tradition of sublimation and the theories of creativity in works of the four greatest Russian religious thinkers: Solovyov, Rozanov, Berdyaev and Vysheslatsev. Crone's study adds what is missing to the few books that currently exist about the use of psychoanalysis in Russia. It shows how the sexual theories of creativity /sublimation of Solovyov and Rozanov led to the concepts of Berdyaev and Vysheslatsev.